Gorska (Festuca drymeja) in gozdna bilnica (Festuca altissima) - pomembna diferencialna indikatorja gozdnih združb - Cimperšek, Mitja (Gozdarski vestnik, 2011)
Among numerous species of the Festuca genus there are also two dominant builders of forest associations: mountain (F. drymeja) and wood fescue (F. altissima). While mountain fescue grows in the sub-montane forests of the South-Western Europe, associations with wood fescue are more frequent in the montane areas of the Central Europe. Mountains of Boč, Donačka gora and Maceljrepresent a special geologic, climate, floristic and vegetation meeting point of Slovenia, where the most forest association with the mentioned fescues are found. Comparing areal prevalence and using Ellenberg method of phytoindication we studied their ecological specialties. Despite their minute morphological differences and a similar ecological amplitude, their associations feature differences that are also reflected in their differentiated forest management treatment.
Keywords: trave; gorska bilnica; gozdna bilnica; areali; fitoindikacija; ecology; ekologija; obnova gozdov